Evaluation of Drought Characteristics in Iraq using SC-PDSI - Jawad, Thaer K.; Al-Taai, Osama T.; Al-timimi, Yaseen K. (Science Journal of University of Zakho, 2018)
Evaluation of drought characteristics in Iraq by analysis annual growing season of Self-Calibrating Palmer Drought Severity Index (SC-PDSI) for three climatic zones using run theory method. The efficiency of SC-PDSI for drought monitoring was examined from compared with Rainfall Departure from the mean (RD) for three zones (Arid and Semi-Arid, Steppes and Desert) for the period 1981-2015, were derived from Climatic Research Unit (CRU). The spatial interpolation techniques in ArcGIS package has been used, to cover the whole extent of country and extracting the zones. Statistical methods were applied to compute the probability of drought events at every zone. The results showed the years 1999, 2000, 2008 and 2009 experienced droughts in all zones except the desert zone where was experienced severe drought in 2012, while the years 1982 and 1988 experienced received precipitation above-average in all zones. The values of standard deviation of precipitation were compared with precipitation anomalies for each zone, the drier seasons are (2007-2008) and (1998-1999) in all Zones. The wetter seasons are (1987-1988) in Arid and Semi-Arid and Steppes zone, (1994-1995) and (1997-1998) are wetter seasons in Desert zone. Using run theory, the steppes zone have experienced more severe droughts than other zones evaluated in this study and the most susceptible areas to dry spell are steppes and Arid and Semi-Arid Zones during study period. While the desert zone experienced less droughts.